A Retrospective Study of Urinary Schistosomiasis in the Eastern Cape Province, South Africa - Dominic Targema Abaver (Tropical Medicine and Infectious Disease)
Schistosomiasis is caused by infection with trematode flukes of the genus Schistosoma. More than 700 million people worldwide are estimated to be susceptible to infection. In sub-Saharan Africa, schistosomiasis is the second most widespread neglected tropical disease after malaria. This retrospective investigation evaluated the incidence and impacts of schistosomiasis on communities across three major districts of the Eastern Cape province in South Africa using a cross-sectional retrospective observational analysis of secondary data from patients with microscopically confirmed schistosomiasis between 2019 and 2020. This study focused upon both rural and semi-urban areas, including Bizana, Butterworth, Centane, Elliotdale, Flagstaff, Idutywa, Lusikisiki, Libode, Mqanduli, Port St. Johns, Willowvale, and Mthatha. Data were obtained from three districts—Alfred Nzo, Amatole, and OR Tambo—covering both rural and semi-urban regions. This study included patients of all ages who submitted urine samples for schistosomiasis testing in the specified districts. A simple random sampling method was used to select 337 clinical records from the National Health Laboratory Service (NHLS) of Mthatha. Hospital records from the NHLS Microbiology Department of Mthatha were analyzed. St Barnabas Laboratory had the highest frequency of cases (34.1%), followed by Greenville Depot (17.8%) and Willowvale Laboratory (11.3%). Most cases were in the 10–19 age group (63.4%), followed by those under 10 years of age (24.9%). Male patients constituted 76.4% of the cases, while female patients accounted for 23.6%. Viable ova were observed in 98.2% of the samples. This study highlights a significant prevalence of schistosomiasis in the Eastern Cape province, with a higher incidence in rural areas and among males aged 10–19. These findings underscore the need for targeted public health interventions and continuous monitoring to control and prevent schistosomiasis in this region.